Efficient Privacy-Preserving Authentication using Blockchain for VANET - Pariyarath, Akhil; Tomar, Shubham; Tripathi, Meenakshi (International Conference on Communication Systems and Networks (Online), 2023)
A vehicular Ad-hoc Network is a wireless network that provides comfort while driving and enhances safety. A tremen-dous amount of information is exchanged between vehicles and roadside units. While exchanging information, we should prevent others from identifying the subject of communication or learning one's location[1]. The current privacy-preserving approaches for Vehicular Ad-hoc Networks (VANETs) generally maintain many pseudonyms[2] for a single vehicle, neglecting to consider the need for a secret identity. These authentication approaches make managing pseudonyms challenging and revocation inefficient. We analyzed this issue and proposed a privacy-preserving protocol using blockchain[3]. Our proposed protocol is implemented in the Polygon testbed(i.e., Mumbai Testnet), which keeps the vehicle's identity confidential. This method reduces the verification time and cost of the vehicles when compared with other approaches.